Low-cement eco-concrete and the role of recycled concrete aggregates (RCA), supplementary cementitious materials (SCMs), and other additives in improving sustainability and durability - N. Brioschi; E. Giner Cordero; S. Ng; C. Paglia (Materiales de Construccion)
This study focuses on the development of low-cement eco-concretes incorporating recycled concrete aggregates (RCA) and waste materials such as wood ashes, aiming to achieve a balance between sustainability and mechanical performance. Different concrete mixes were designed with varying cement content (240–290 kg/m3) and RCA replacement levels (25%–50% by weight). The materials used included II/A-LL 42.5 R cement, natural calcareous-silica aggregates, RCA from C30/37 concrete, wood waste ashes, and limestone filler. Experimental tests were conducted on fresh and hardened concrete, including workability, compressive strength, elastic modulus, carbonation resistance, freeze-thaw durability, and chloride penetration resistance. Results show that the mixtures with RCA demonstrated similar or better performance compared to conventional concrete, with C6 (using wood ashes from the burner) showing promising compressive strength and durability characteristics. The study demonstrates that these low-cement mixtures, using recycled aggregates and supplementary materials, can meet the durability requirements for sustainable infrastructure applications.